The colonization processes of Myrtus communis by strains of Pseudomonas savastanoi with a differential ability to produce phytohormones. (14th April 2019) - Schiff, S.; Tani, C.; Cimmino, A.; Mandalà, G.; Cinelli, T.; Evidente, A.; Fiori, M.; Surico, G.; Marchi, G.
Abstract : The ability to produce indole‐3‐acetic acid (IAA) through the indole‐3‐acetamide (IAM) pathway as well as cytokinins is a common trait of Pseudomonas savastanoi populations causing disease on oleander and olive. These phytohormones are required for the induction and development of an outgrowth of plant cell tissue termed a knot. However, in myrtle orchards of Sardinia (Italy), strains of P. savastanoi unable to produce cytokinins were found coexisting with cytokinin‐producing strains. Data presented here show that the ability to produce IAA through the IAM pathway is also a variable trait within this population, raising questions on the exact role of these plant growth substances in the disease process on myrtle. Three P. savastanoi strains were selected based on their differential ability to produce phytohormones in vitro, and their interaction with the host was investigated over a period of 8 months using histological methods. All strains successfully invaded the infected twigs, moving systemically (unhalted by host defences) upward and downward from the inoculation point, both by completely degrading the cell walls and by taking advantage of the xylem vessels and intercellular spaces. Moreover, all strains induced the development of cankers, which slowly evolved into typical knots only on the twigs inoculated with the phytohormone‐producing strains. This study further demonstrates that cytokinins and IAA are essential for knot development; moreover, it ascertains that bacterial production of cytokinins is not necessary for host colonization and for the expression of pathogenicity (i.e. the ability to cause disease) of P. savastanoi on myrtle.